Multiple herbicide resistance evolution: The case of eleusine indica in Brazil - Vázquez-García, José (2021)
The occurrence of multiple herbicide resistant weeds has increased considerably in glyphosate-resistant soybean fields in Brazil; however, the mechanisms governing this resistance have not been studied. In its study, the target-site and nontarget-site mechanisms were characterized in an Eleusine indica population (R-15) with multiple resistance to the acetyl-CoA carboxylase (ACCase) inhibitors, glyphosate, imazamox, and paraquat. Absorption and translocation rates of 14C-diclofop-methyl14C-imazamox and 14C-glyphosate of the R-15 population were similar to those of a susceptible (S-15) population; however, the R-15 population translocated ∼38% less 14C-paraquat to the rest of plant and roots than the S-15 population. Furthermore, the R-15 plants metabolized (by P450 cytochrome) 55% and 88% more diclofop-methyl (conjugate) and imazamox (imazamox−OH and conjugate), respectively, than the S-15 plants. In addition, the Pro-106-Ser mutation was found in the EPSPS gene of this population. This report describes the first characterization of the resistance mechanisms in a multiple herbicide resistant weed from Brazil.